Evaluation of Patients Who Referred to Emergency Department with Dermatologic Complaints - Tayfun ÖZTÜRK; Ömer Levent AVŞAROĞULLARI; Murat BORLU; Bahadır TAŞLIDERE (Namık Kemal Tıp Dergisi, 2019)

(untitled)
Aim:The aim of this study was to give information about demographic and clinical characteristics, consultation, discharge, hospitalization rates and life-threatening clinical presentations of patients presenting to the Emergency Department with dermatological complaints.Materials and Methods:The study prospectively included patients older than 16 who were admitted to Erciyes University Hospital Emergency Department with dermatological complaints between. The evaluated parameters were age, gender, patients history, complaint, complaint onset, the period spent until admission, type of lesion, diagnosis, consultations, hospitalization, and discharge status.Results:A total of 400 patients were included in the study. Patients who presented with dermatological complaints represented %0.70 of all patients admitted to the Emergency Department. 221 (55%) of the patients were female with a mean age of 38.6 years. Skin redness was the most common cause of admission (29.8%) and urticaria was the most common diagnosis (54.3%). 48.3% of the patients applied to the emergency department at least 24 hours after the onset of symptoms. 31% of the patients were consulted. ‘True dermatological emergencies’ such as necrotizing fasciitis, toxic epidermal necrolysis, and erythema multiforme, were diagnosed in only three patients (0.75%). 19% of the patients were hospitalized and the most common diagnosis was cellulitis (30.8%). The body surface area of the lesion alone did not affect the rate of hospitalization.Conclusion:The proportion of patients presenting with dermatological complaints to the Emergency Department is limited. Especially, patients with accompanying life-threatening systemic organ involvement should be hospitalized.